Market Opportunities and Challenges: A Case Study of Tesco - Muhammad Raqib Aiman Bin Rosnizam; Daisy Mui Hung Kee; Muhammad Ekmal Haikal Bin Mohammad Akhir; Misha Shahqira; Muhammad Amril Hanif Bin Mohd Yusoff; Roland Satrya Budiman; Aisha Mohammad Alajmi (AIBPM Publisher, 2020)
Tesco is one of the world’s leading multinational grocery and general merchandise retailers that was founded in 1919. Tesco opened its first hypermarket in Burnt Oak, England in 1931. Tesco has expanded rapidly in different countries such as Malaysia, Hungary, and Thailand. For decades, it has been the people' go-to hypermarket. The success of Tesco was because of its low prices and the varieties of products. Tesco has diversified into areas such as the retailing of books, clothing, furniture, and electronics. Despite the undeniable success, Tesco faces setbacks such as the accounting scandal, horsemeat scandal, and the downward shift in quality and services. This paper will show the improvements that can be made to handle the situations.